The Influence of Liquidity on Capital Structure and Company Value in Transportation Companies During the Covid-19 Pandemic - Arfandi; Nurhani (www.amertainstitute.com, 2024)
This study investigates the influence of liquidity on capital structure and firm value among transportation companies listed on the Indonesia Stock Exchange (IDX) during the Covid-19 pandemic. Using a quantitative approach, data were collected from 25 transportation companies over the period from 2020 to 2022. The findings reveal a positive and significant effect of liquidity on firm value. However, liquidity does not act as a mediator between liquidity and capital structure, indicating a more complex relationship. The Covid-19 pandemic caused a significant decline in the performance of transportation companies, adversely affecting their liquidity levels and investment decisions, which, in turn, impacted firm value. Companies with higher liquidity were better positioned to meet short-term obligations, thereby enhancing creditor confidence. This trust is crucial for companies seeking external financing, as creditors are more likely to support firms with strong liquidity management. However, high liquidity does not always result in positive outcomes. Poor liquidity management can strain financial resources, potentially increasing the cost of capital and hindering long-term growth. This study highlights the importance of efficient liquidity management for financial managers, providing valuable insights into the balancing act between maintaining adequate liquidity for operational needs and optimizing capital structure for growth. For investors, these findings offer guidance in evaluating company health, particularly during economic downturns like the pandemic. Understanding liquidity’s role in shaping firm value can assist in making informed investment decisions. Ultimately, this study contributes to the body of knowledge on financial management in the transportation sector, offering strategies for enhancing resilience and competitiveness in the post-pandemic business environment.